Yargıda stratejik yönetim - Bağcı, İbrahim (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2011)
Adli yargıda startejik yönetim uygulamalırında tespit edilen sorunlar ve çözüm önerileri

In this study, Turkish judical judiciary to take decsions more quickly and fairleyy for the work of the strategic planning and management aimed to make a contribution
Judical strategic management
Keywords: İşletme; Business Administration